Development of a Student Social Anxiety Model Based on Uncompromising Perfectionism and Experiential Avoidance with a Mediating Role of Difficulty in Emotion Regulation - Mohamad Hatami Nejad; Mohammadreza Noroozi Homayoon; Masoud Sadeghi; Esmail Sadri Damirchi (پژوهش‌های کاربردی روانشناختی)
The current research was conducted to formulate students' social anxiety models based on uncompromising perfectionism, experiential avoidance, and the mediating role of difficulty in emotion regulation. The method of descriptive-correlational research was structural equation modeling. The statistical population of the research included all high school students in Khorramabad city. 350 students were selected by random cluster sampling method, and social anxiety questionnaires (SPIN), perfectionism (PI), experience avoidance (AAQ), and difficulty in emotion regulation (DERS) were completed. SPSS22 software and Amos26 path analysis were used to analyze descriptive and correlational data. The results showed that the proposed model has a good fit, and the findings also showed that uncompromising perfectionism and experiential avoidance both directly and indirectly play a mediating role in regulating emotion and social anxiety in students. Is a transition. The results of the Bootstrap test confirmed the indirect role of difficulty in emotion regulation and the indirect effect of this psychological factor on students' social anxiety. Therefore, according to the results obtained from the research, it can be concluded that to control the level of social anxiety of students, necessary interventions and training should be done to regulate emotions, establish effective communication with other students, and increase self-awareness.